First finding of Alternanthera maritima in Europe (Sicily) and considerations on its morphological peculiarities, ecological requirements, and potential invasiveness - Marcenò, Corrado; Iamonico, Duilio; Venanzoni, Roberto; Boschi, Ilaria; Guarino, Riccardo (Mediterranean Botany, 2024)
Alternanthera maritima was found in the southeastern part of Sicily, marking a new floristic record for both Italy and Europe. This paper provides an analysis of the morphological characteristics observed in the collected specimens and explores the ecological features of the community where they were found. Also, we discuss the taxonomic criticality of the genus and assess the risk that the new finding may become invasive.